Processing and preparing method of novel nickel-titanium alloy nasolacrimal duct stent

Through the processing and preparation of nickel-titanium alloy materials, the shortcomings in strength and flexibility of existing nasolac duct support were solved, and high-precision nasolac duct support suitable for adults and children were prepared, achieving high strength and flexibility of the support , meets the mechanical performance requirements of nasolac duct support.

CN119304525AActive Publication Date: 2025-01-14SHENZHEN NATAI MEDICAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411470887.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-14
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

There are shortcomings in the strength and flexibility of existing nasolar duct support, especially in the treatment of nasolar duct obstruction in children, existing materials such as silicone are not sufficient in mechanical support, and are difficult to process and are prone to disengage or displace.

Method used

Using NiTi alloy materials, high-precision and multi-specimen nickel-titanium alloy nasolac tubes are prepared through steps such as straightening, mechanical drilling, polishing, cold rolling deformation, hot drawing deformation, multi-process coupled heat treatment and femtosecond laser cutting. stents to improve their mechanical properties and biocompatibility.

Benefits of technology

The high strength, flexibility and excellent mechanical properties of the nickel-titanium alloy nasolac duct support are achieved. It is suitable for adults and children, meets the needs of nasolac duct support, and achieves the precise forming of the support through precise cutting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119304525A_ABST
    Figure CN119304525A_ABST
Patent Text Reader

Abstract

The invention provides a processing and preparing method of a novel nickel-titanium alloy nasolacrimal duct stent, and relates to the technical field of medical instruments. The method comprises the following steps: S1, obtaining a nickel-titanium alloy bar, and straightening the nickel-titanium alloy bar; s2, the straight rod is subjected to mechanical drilling machining; s3, the inner surface and the outer surface of the rough pipe blank are polished; s4, cold rolling deformation is conducted on the rough pipe blank through a hard core rod; s5, carrying out hot drawing deformation on the pipe blank by adopting a hard core rod; s6, a soft core rod is adopted for conducting room-temperature drawing deformation on the pipe blank; s7, carrying out multi-process coupling heat treatment on the pipe; s8, centerless grinding and electrochemical polishing are conducted on the pipe; and S9, the pipe is subjected to laser cutting and vacuum heat treatment. According to the invention, excellent surface roughness can be provided for the pipe, the density of the pipe can be effectively improved, the concentricity of the pipe can be improved, the inner surface roughness of the pipe can be effectively improved, the quality of the pipe can be improved, and the hyperelasticity is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical devices, and in particular to a processing and preparation method of a novel nickel-titanium alloy nasolacrimal duct stent. Background Art

[0002] Nasolacrimal duct obstruction and chronic dacryocystitis are both common eye diseases in adults, and congenital nasolacrimal duct obstruction is also a common eye disease in children. Both can easily cause clinical symptoms such as epiphora, which have a great impact on patients' daily lives. Combined infection poses a great threat to the safety of the eyeball.

[0003] Nasolacrimal duct obstruction in adults is mainly treated with lacrimal duct probing and nasolacrimal cystostomy. Compared with lacrimal duct incision, lacrimal duct probing is less invasive, simple to operate, and has good efficacy, but the long-term effect is unstable and the recurrence rate is high. It is particularly unsuitable for the treatment of chronic dacryocystitis, which limits its application. Nasolacrimal cystostomy has better effects and a higher success rate, but the operation is more complicated, with more bleeding during the operation, a long operation time, and scars on the face after the operation. Sometimes the operation cannot be performed due to surgical contraindications. At the same time, the operation changes the original anatomical channel of the lacrimal duct. One day after the operation, the fibers of the anastomosis form scars or ossification, which can easily cause anastomotic obstruction and even re-obstruction of the lacrimal duct, losing the opportunity for another operation. Nasolacrimal duct obstruction in children is mostly caused by incomplete degeneration of the embryonic residual membrane of the nasolacrimal duct opening, and is generally treated with lacrimal cyst massage and lacrimal duct probing.

[0004] In order to reduce surgical damage and not change the original anatomical channel of the tear duct, a treatment method using silicone nasolacrimal duct stents has emerged to place a permanent tear channel between the lacrimal sac and the inferior nasal meatus. Compared with traditional surgery, the installation of nasolacrimal duct stents is simple to operate, minimally invasive, does not change the original anatomical position, does not leave scars after surgery, and has a wide range of indications.

[0005] The tear duct structure is curved, so it is necessary not to damage the tear duct, and at the same time, it needs to be flexible and elastic. Most of the existing nasolacrimal duct stents have a curved structure in the fixed part, and the raw material is mainly silicone. However, when the strength of silicone is not enough, it has the major defect of being easy to fall out and shift. Therefore, a nasolacrimal duct stent with higher mechanical support than silicone is needed. At the same time, due to the limitation of raw materials, there are no related products for pediatric nasolacrimal duct stents.

[0006] The applicant has found that there are at least the following technical problems in the prior art: In view of the existing technical conditions, nickel-titanium alloy nasolacrimal duct stents can be used to solve the above clinical problems. High-precision, thin-diameter, thin-walled nickel-titanium alloy tubes have high strength and radial support force, special shape recovery ability, and are widely used in minimally invasive surgical instruments, especially interventional intracavitary stents. They are the key material for the preparation of nickel-titanium alloy nasolacrimal duct stents. However, nickel-titanium alloy has a large deformation resistance at room temperature, a fast work hardening rate, and poor plastic deformation ability. The tube is prone to cracking during cold deformation. Therefore, the forming problem of this type of alloy tube has always been a difficulty in the field of plastic processing. Summary of the invention

[0007] The purpose of the present invention is to provide a novel method for processing and preparing a nickel-titanium alloy nasolacrimal duct stent to solve the technical problems existing in the prior art. The preferred technical solutions among the many technical solutions provided by the present invention can produce many technical effects as described below.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] A novel method for processing and preparing a nickel-titanium alloy nasolacrimal duct stent comprises the following steps:

[0010] S1, obtaining a nickel-titanium alloy bar, and straightening the nickel-titanium alloy bar to form a straight bar;

[0011] S2, mechanically drilling the straight rod to form a rough tube blank;

[0012] S3, polishing the inner surface and outer surface of the rough tube blank;

[0013] S4, using a hard mandrel to cold-roll the rough tube to form a tube with a diameter of 4.0-8.0 mm;

[0014] S5, using a hard mandrel to perform hot drawing deformation on the tube blank to form a tube blank with a diameter of Φ1.0-4.0 mm;

[0015] S6, using a soft mandrel to perform room temperature drawing deformation on the tube blank to form a tube with a diameter of Φ0.25-2.0 mm;

[0016] S7, performing multi-process coupled heat treatment on the pipe;

[0017] S8, performing centerless grinding on the pipe and electrochemical polishing on the pipe;

[0018] S9. Laser cutting the tube and vacuum heat treatment the tube to obtain a novel nickel-titanium alloy nasolacrimal duct stent.

[0019] Preferably, the nickel-titanium alloy bar in step S1 is prepared according to the following mass percentages: Ni is 54.5-57.0%, C≤0.04%, Co≤0.05%, Cu≤0.01%, Cr≤0.01%, H≤0.005%, Fe≤0.05%, Nb≤0.025%, N≤0.005%, O≤0.04%, and the balance is Ti;

[0020] The fixed length of the nickel-titanium alloy bar is 1-4m. After being cut into the fixed length, it is straightened by a straightening device, and the straightness after straightening is not greater than 0.5mm / m.

[0021] Preferably, in step S2, before mechanical drilling is performed on the straight rod, the straight rod is further processed into a fixed length after being straightened.

[0022] Preferably, in step S3, a mechanical polishing device is used to polish the inner surface and the outer surface of the rough tube blank, and the roughness of the inner surface after polishing is not greater than 1.6 μm, and the roughness of the outer surface is not greater than 1.0 μm.

[0023] Preferably, in step S4, the material of the hard core rod is cemented carbide, the hard core rod is inserted into the rough tube blank to obtain an assembly, and the assembly is cold-rolled and deformed by cold rolling equipment, and the deformation amount of a single pass is less than 13%. After the deformation amount is 25%-50%, intermediate vacuum annealing is performed, and after multiple cycles, a tube blank of Φ4.0-8.0 mm is formed.

[0024] Preferably, in step S5, the material of the hard core rod is cemented carbide, the hard core rod is inserted into the tube blank to obtain a combination, and the combination is subjected to hot drawing deformation by a hot drawing device, the deformation amount of a single pass is less than 15%, and intermediate annealing is performed after the deformation amount is 30%-60%, and a tube blank of Φ1.0-4.0 mm is formed after multiple cycles.

[0025] Preferably, in step S6, the material of the soft mandrel is a material with a Vickers hardness of less than 100, the soft mandrel with a surface coated with molybdenum disulfide lubricant is inserted into the tube blank to obtain an assembly, and the assembly is cold-drawn by room temperature drawing equipment, with a single-pass deformation amount of less than 20%, and intermediate annealing is performed after the deformation amount is 30%-60%, and after multiple cycles, an assembly of Φ0.25-2.0 mm is formed, and then the assembly is cored to obtain a Φ0.25-2.0 mm tube.

[0026] Preferably, in step S7, the pipe is heat treated by a multi-process coupling method of electric pulse treatment and aging treatment.

[0027] Preferably, in step S8, when the tube is electrochemically polished, the polishing liquid consists of 15-25% perchloric acid and 75-85% glacial acetic acid by volume, respectively, the constant voltage is 5-20V, the electrolytic polishing is performed at room temperature, the polishing time is 1-30 minutes, and the roughness of the inner surface after polishing is less than 1.0μm, and the roughness of the outer surface is less than 0.5μm.

[0028] Preferably, in step S9, the tube is first cut into a corresponding length of the nasolacrimal duct stent, and then femtosecond laser cutting is performed, and then the tube is vacuum heat treated at a temperature of 400-600°C and a heat treatment time of 10-50 minutes, and then furnace cooling or water cooling is used for cooling.

[0029] The beneficial effects of the present invention are: by adopting a mechanical perforation processing method and a polishing processing method for the inner surface and the outer surface of the pipe, the pipe is provided with excellent surface roughness, thereby facilitating subsequent processing and use;

[0030] By adopting the cold rolling deformation processing method, the density of the pipe can be effectively improved and the concentricity of the pipe can be improved;

[0031] By using a combination of a hard core rod and a soft core rod to perform hot drawing deformation and room temperature drawing deformation respectively, the inner surface roughness of the pipe can be effectively improved and the quality of the pipe can be improved;

[0032] By adopting a multi-process coupled heat treatment method to heat treat the finished pipes, the pulse current can interact with defects such as lattice distortion, vacancies, dislocations, grain boundaries, etc., so that the microstructure of the nickel-titanium alloy gradually tends to be uniform and stable, and a good stress platform appears. Low-temperature aging treatment precipitates a large number of small and evenly distributed Ni4Ti3 particles, and the superelasticity is significantly improved.

[0033] The present invention can produce nickel-titanium alloy tubes and nasolacrimal duct stents of various specifications, and provide nickel-titanium alloy raw materials for ophthalmic and otolaryngological medical devices;

[0034] The present invention can meet the flexibility and support force required by the nasolacrimal duct stent by utilizing the superelasticity and excellent mechanical properties of nickel-titanium alloy. At the same time, nickel-titanium alloy also has excellent biocompatibility, which meets the requirements of the nasolacrimal duct stent for raw material performance;

[0035] The present invention uses femtosecond laser to precisely cut out the stent structure, thereby achieving accurate stent forming, thereby preparing a qualified nasolacrimal duct stent;

[0036] The present invention can adjust the product size so that the produced nasolacrimal duct stent is suitable for both adults and children. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION

[0039] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0040] In the description of the present invention, it should be understood that the terms "center", "lateral", "length", "width", "height", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "side" and the like indicate positions or positional relationships based on the attached Figure 1 The orientation or positional relationship shown is only for the convenience of describing the present invention and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0041] In the description of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to the specific circumstances.

[0042] Reference Figure 1 The present invention provides a novel method for processing and preparing a nickel-titanium alloy nasolacrimal duct stent, comprising the following steps:

[0043] S1, obtaining a nickel-titanium alloy bar, and straightening the nickel-titanium alloy bar to form a straight bar;

[0044] Specifically, the nickel-titanium alloy bar is preferably formulated according to the following mass percentages: Ni is 54.5-57.0%, C≤0.04%, Co≤0.05%, Cu≤0.01%, Cr≤0.01%, H≤0.005%, Fe≤0.05%, Nb≤0.025%, N≤0.005%, O≤0.04%, and the balance is Ti;

[0045] The diameter of the nickel-titanium alloy rod is preferably 7-25 mm, and the cut length of the nickel-titanium alloy rod is preferably 1-4 m. After being cut into the required cut length, it is straightened using a straightening device, and the straightness after straightening is no greater than 0.5 mm / m.

[0046] S2, mechanically drilling the straight rod to form a rough tube blank;

[0047] Specifically, before mechanical drilling is performed on the straight bar, the straight bar needs to be processed into a fixed length after straightening, where the fixed length is the required appropriate length;

[0048] Then, the straight rod is prepared into a nickel-titanium alloy tube blank by a deep drilling process, and the ratio of the inner and outer diameters of the nickel-titanium alloy tube blank is 0.30-0.86.

[0049] S3, polishing the inner surface and outer surface of the rough tube blank;

[0050] Specifically, the inner surface and the outer surface of the rough tube blank are polished by mechanical polishing equipment. In the process of polishing the outer surface, the mechanical polishing equipment used includes but is not limited to a centerless grinder and a belt polisher. The roughness of the outer surface after polishing is not greater than 1.0 μm.

[0051] In the process of polishing the inner surface, the mechanical polishing equipment used includes but is not limited to abrasive flow equipment, pickling or electrolytic polishing equipment, and the roughness of the inner surface after polishing is not greater than 1.6 μm.

[0052] S4, using a hard mandrel to cold-roll the rough tube billet to form a tube billet of Φ4.0-8.0 mm;

[0053] Specifically, the material of the hard core rod is preferably cemented carbide. The hard core rod is first inserted into the rough tube blank to obtain an assembly, and then the assembly is cold-rolled and deformed by cold rolling equipment. The deformation amount of a single pass is less than 13%. After the deformation amount is 25%-50%, intermediate vacuum annealing is performed. After multiple cycles, a tube blank of Φ4.0-8.0mm is formed.

[0054] S5. Use a hard mandrel to perform hot drawing deformation on the tube blank to form a tube blank of Φ1.0-4.0mm;

[0055] Specifically, the material of the hard core rod is preferably cemented carbide. The hard core rod is first inserted into the tube blank to obtain an assembly, and then the assembly is hot-drawn and deformed using a hot drawing device. The deformation amount of a single pass is less than 15%. After the deformation amount is 30%-60%, intermediate annealing is performed. After multiple cycles, a tube blank of Φ1.0-4.0mm is formed.

[0056] S6. Use a soft mandrel to perform room temperature drawing deformation on the tube blank to form a tube with a diameter of Φ0.25-2.0 mm;

[0057] Specifically, the material of the soft core rod is preferably a material with a Vickers hardness of less than 100, such as red copper. The soft core rod with a surface coated with molybdenum disulfide lubrication is first inserted into the tube blank to obtain an assembly, and then the assembly is cold-drawn using room temperature drawing equipment. The single-pass deformation amount is less than 20%, and intermediate annealing is performed after the deformation amount is 30%-60%. After multiple cycles, an assembly of Φ0.25-2.0 mm is formed, and then the assembly is cored to obtain a Φ0.25-2.0 mm tube.

[0058] S7, performing multi-process coupled heat treatment on the pipe;

[0059] Specifically, the pipe is heat treated by a multi-process coupling method of electric pulse treatment and aging treatment.

[0060] S8. Perform centerless grinding on the pipe and electrochemical polishing on the pipe;

[0061] Specifically, when the pipe is electrochemically polished, the polishing liquid is composed of 15-25% perchloric acid and 75-85% glacial acetic acid by volume, the constant voltage is 5-20V, the electrolytic polishing is carried out at room temperature, the polishing time is 1-30 minutes, the roughness of the inner surface after polishing is less than 1.0μm, and the roughness of the outer surface after polishing is less than 0.5μm.

[0062] S9, laser cutting the tube, and vacuum heat treatment the tube to obtain a new nickel-titanium alloy nasolacrimal duct stent;

[0063] Specifically, the tube is first cut into the corresponding length of the nasolacrimal duct stent, and then femtosecond laser cutting is performed. During the femtosecond laser cutting process, the pulse width is 50-600fs, the pulse energy is 30-160μJ, the pulse repetition frequency is 80-500kHz, the cutting speed is 0.2-4.0mm / s, and the cutting is performed under a protective atmosphere;

[0064] The pipe is then subjected to vacuum heat treatment at a temperature of 400-600°C for 10-50 minutes, and then cooled by furnace cooling or water cooling.

[0065] The present invention adopts a mechanical perforation processing method in step S2, and adopts a polishing processing method for the inner surface and outer surface of the pipe in steps S3 and S8, thereby providing the pipe with excellent surface roughness, thereby facilitating subsequent processing and use;

[0066] The present invention adopts a cold rolling deformation processing method in step S4, which can effectively improve the density of the pipe and improve the concentricity of the pipe;

[0067] The present invention uses a hard core rod and a soft core rod in combination in steps S5 and S6 to perform hot drawing deformation and room temperature drawing deformation respectively, which can effectively improve the inner surface roughness of the pipe and improve the quality of the pipe.

[0068] The present invention adopts a multi-process coupled heat treatment method to heat treat the finished pipe in step S7. The pulse current can interact with defects such as lattice distortion, vacancies, dislocations, grain boundaries, etc., so that the microstructure of the nickel-titanium alloy gradually tends to be uniform and stable, and a good stress platform appears. Low-temperature aging treatment precipitates a large number of small and uniformly distributed Ni4Ti3 particles, and the superelasticity is significantly improved.

[0069] The present invention provides a novel method for processing and preparing a nickel-titanium alloy nasolacrimal duct stent, by which nickel-titanium alloy tubes and nasolacrimal duct stents of various specifications can be produced, providing nickel-titanium alloy raw materials for ophthalmic and otolaryngological medical devices;

[0070] The present invention can meet the flexibility and support force required by the nasolacrimal duct stent by utilizing the superelasticity and excellent mechanical properties of nickel-titanium alloy. At the same time, nickel-titanium alloy also has excellent biocompatibility, which meets the requirements of the nasolacrimal duct stent for raw material performance;

[0071] The present invention uses femtosecond laser to precisely cut out the stent structure, thereby achieving accurate stent forming, thereby preparing a qualified nasolacrimal duct stent;

[0072] The present invention can adjust the product size so that the produced nasolacrimal duct stent is suitable for both adults and children.

[0073] The present invention provides three embodiments and four comparative embodiments, wherein:

[0074] Comparative Example 1 was not polished, and a non-mechanical drilling method was used to open the hole;

[0075] Comparative Example 2 is a case where no cold rolling deformation is performed;

[0076] Comparative Example 3 is to use the traditional method to perform cold drawing deformation;

[0077] Comparative Example 4 adopts the traditional method to perform annealing heat treatment, and does not perform multi-process coupling heat treatment.

[0078] Embodiment 1

[0079] This embodiment provides a novel method for processing and preparing a nickel-titanium alloy nasolacrimal duct stent, comprising the following steps:

[0080] Step S1, the nickel-titanium alloy rod is made according to the following mass percentage: Ni is 56.14%, C is 0.0078%, Co: <0.005%, Cu: <0.005%, Cr: <0.005%, H: <0.0016%, Fe: <0.005%, Nb: <0.002%, N: <0.003%, O: 0.029%, and the remainder is Ti. The diameter of the nickel-titanium alloy rod is 20 mm, and the fixed length is 3 m. After cutting, it is straightened by electric straightening equipment. The straightness of the rod after straightening is 0.3 mm / m.

[0081] Step S2, the straightened bar is cut into a fixed length of 600 mm, and the bar is drilled using a deep hole processing device, and the inner hole diameter of the tube blank is 14.0 mm.

[0082] Step S3, polishing the outer surface of the tube blank by a centerless grinder, and polishing the inner surface of the tube blank by an abrasive flow device. After grinding and polishing, the roughness of the outer surface of the tube blank is 0.45 μm, and the roughness of the inner surface is 0.75 μm.

[0083] Step S4, using cemented carbide as a hard core rod, and evenly coating the surface of the hard core rod with an oil lubricant, inserting the hard core rod into the tube blank to obtain an assembly, deforming the assembly by cold rolling, and controlling the deformation amount of a single pass to be 10%. When the total deformation amount reaches 30%, performing intermediate vacuum annealing on the tube, the annealing temperature is 750° C., the time is 5 min, and the cycle is repeated for multiple times to obtain a tube blank with an outer diameter of 8.0 mm and an inner diameter of 5.1 mm.

[0084] Step S5, using cemented carbide as a hard core rod, and evenly coating the surface of the hard core rod with an oil lubricant, inserting the hard core rod into the tube blank to obtain an assembly, and deforming the assembly by hot drawing, the hot drawing temperature is 780° C., the speed is 5 m / min, and the single-pass deformation is controlled at 12%. When the total deformation reaches 40%, the tube is intermediate annealed at a temperature of 750° C. for 1 min, and the cycle is repeated for multiple times to obtain a tube blank with an outer diameter of 2.0 mm and an inner diameter of 1.95 mm.

[0085] Step S6, using red copper as a soft core rod, evenly coating the surface of the soft core rod with molybdenum disulfide, inserting the soft core rod into the tube blank to obtain an assembly, using room temperature drawing equipment to continuously cold draw the assembly, and controlling the deformation of a single pass to be 15%. When the total deformation reaches 45%, performing intermediate annealing on the assembly at a temperature of 650° C. for 1 min, repeating the process for multiple times to obtain an assembly with an outer diameter of 0.3 mm and an inner diameter of 0.21 mm, and then removing the soft core rod to obtain a tube.

[0086] Step S7, performing a multi-process coupled heat treatment of electric pulse treatment + aging treatment on the pipe, the electric pulse treatment process parameters are duty cycle P of 0.09, pulse frequency f of 150 Hz, and on-time of 600 μs, and the aging treatment process parameters are temperature of 250° C. and time of 24 h.

[0087] Step S8, the outer surface of the pipe is centerlessly ground, and then the pipe is electrochemically polished. The polishing liquid consists of 21% perchloric acid (HCLO4, content 70.0-70.2%) and 79% glacial acetic acid (CH3COOH, content not less than 99.5%) by volume fraction. The electrolytic polishing is performed at a constant voltage of 10V and room temperature for 10 minutes. The roughness of the outer surface of the pipe after polishing is 0.21μm, and the roughness of the inner surface is 0.65μm.

[0088] Step S9, cutting the nickel-titanium alloy tube into a length of 80 mm, and then performing femtosecond laser cutting on it, setting the pulse width to 337 fs, the pulse energy to 80 μJ, the pulse repetition frequency to 100 kHz, the cutting speed to 0.8 mm / s, and cutting under helium. After cutting, the heat treatment temperature is 480°C for 26 min, and then furnace cooling is adopted to finally obtain a finished nickel-titanium alloy nasolacrimal duct stent.

[0089] Embodiment 2

[0090] This embodiment provides a novel method for processing and preparing a nickel-titanium alloy nasolacrimal duct stent, comprising the following steps:

[0091] Step S1, the nickel-titanium alloy rod is made according to the following mass percentage: Ni is 56.14%, C is 0.0078%, Co: <0.005%, Cu: <0.005%, Cr: <0.005%, H: <0.0016%, Fe: <0.005%, Nb: <0.002%, N: <0.003%, O: 0.029%, and the remainder is Ti. The diameter of the nickel-titanium alloy rod is 18 mm, and the fixed length is 3 m. After cutting, it is straightened by electric straightening equipment. The straightness of the rod after straightening is 0.2 mm / m.

[0092] Step S2, the straightened bar is cut into a fixed length of 500 mm, and the bar is drilled using a deep hole processing device, and the inner hole diameter of the tube blank is 10.0 mm.

[0093] Step S3, polishing the outer surface of the tube blank by a centerless grinder, and polishing the inner surface of the tube blank by an abrasive flow device. After grinding and polishing, the roughness of the outer surface of the tube blank is 0.39 μm, and the roughness of the inner surface is 0.81 μm.

[0094] Step S4, using cemented carbide as a hard core rod, and evenly coating the surface of the hard core rod with an oil lubricant, inserting the hard core rod into the tube blank to obtain an assembly, deforming the assembly by cold rolling, and controlling the deformation amount of a single pass to be 9%. When the total deformation amount reaches 35%, performing intermediate vacuum annealing on the tube, the annealing temperature is 800° C., the time is 5 min, and the cycle is repeated for multiple times to obtain a tube blank with an outer diameter of 7.5 mm and an inner diameter of 4.5 mm.

[0095] Step S5, using cemented carbide as a hard core rod, and evenly coating the surface of the hard core rod with an oil lubricant, inserting the hard core rod into the tube blank to obtain an assembly, and deforming the assembly by hot drawing, the hot drawing temperature is 780° C., the speed is 8 m / min, and the single-pass deformation is controlled at 11%. When the total deformation reaches 40%, the tube is intermediate annealed at a temperature of 750° C. for 1 min, and the cycle is repeated for multiple times to obtain a tube blank with an outer diameter of 2.5 mm and an inner diameter of 2.38 mm.

[0096] Step S6, using red copper as a soft core rod, evenly coating the surface of the soft core rod with molybdenum disulfide, inserting the soft core rod into the tube blank to obtain an assembly, using room temperature drawing equipment to continuously cold draw the assembly, and controlling the deformation of a single pass to be 13%. When the total deformation reaches 48%, performing intermediate annealing on the assembly at a temperature of 650° C. for 1 min, repeating the process for multiple times to obtain an assembly with an outer diameter of 0.5 mm and an inner diameter of 0.38 mm, and then removing the soft core rod to obtain a tube.

[0097] Step S7, performing a multi-process coupled heat treatment of electric pulse treatment + aging treatment on the pipe, the electric pulse treatment process parameters are duty cycle P of 0.12, pulse frequency f of 200 Hz, and on-time of 600 μs, and the aging treatment process parameters are temperature of 280° C. and time of 24 h.

[0098] Step S8, the outer surface of the pipe is centerlessly ground, and then the pipe is electrochemically polished. The polishing liquid consists of 15% perchloric acid (HCLO4, content 70.0-70.2%) and 85% glacial acetic acid (CH3COOH, content not less than 99.5%) by volume. The electrolytic polishing is performed at a constant voltage of 10V and room temperature for 8 minutes. The roughness of the outer surface of the pipe after polishing is 0.35μm, and the roughness of the inner surface is 0.68μm.

[0099] Step S9, cutting the nickel-titanium alloy tube into a length of 100 mm, and then performing femtosecond laser cutting on it, setting the pulse width to 460 fs, the pulse energy to 50 μJ, the pulse repetition frequency to 333 kHz, the cutting speed to 2 mm / s, and cutting under helium. After cutting, the heat treatment temperature is 500°C for 20 min, and then furnace cooling is adopted to finally obtain a finished nickel-titanium alloy nasolacrimal duct stent.

[0100] Embodiment 3

[0101] This embodiment provides a novel method for processing and preparing a nickel-titanium alloy nasolacrimal duct stent, comprising the following steps:

[0102] Step S1, the nickel-titanium alloy rod is made according to the following mass percentage: Ni is 55.97%, C is 0.0046%, Co: <0.010%, Cu: <0.005%, Cr: <0.005%, H: <0.001%, Fe: <0.005%, Nb: <0.005%, N: <0.003%, O: 0.032%, and the remainder is Ti. The diameter of the nickel-titanium alloy rod is 24 mm, and the fixed length is 2 m. After cutting, it is straightened by electric straightening equipment. The straightness of the rod after straightening is 0.35 mm / m.

[0103] Step S2, the straightened bar is cut into a fixed length of 500 mm, and the bar is drilled using a deep hole processing device, and the inner hole diameter of the tube blank is 19.0 mm.

[0104] Step S3, polishing the outer surface of the tube blank by a centerless grinder, and polishing the inner surface of the tube blank by an abrasive flow device. After grinding and polishing, the roughness of the outer surface of the tube blank is 0.24 μm, and the roughness of the inner surface is 0.68 μm.

[0105] Step S4, using cemented carbide as a hard core rod, and evenly coating the surface of the hard core rod with an oil lubricant, inserting the hard core rod into the tube blank to obtain an assembly, deforming the assembly by cold rolling, and controlling the deformation amount of a single pass to be 10%. When the total deformation amount reaches 30%, performing intermediate vacuum annealing on the tube, the annealing temperature is 800° C., the time is 6 min, and the cycle is repeated for multiple times to obtain a tube blank with an outer diameter of 10.0 mm and an inner diameter of 6.4 mm.

[0106] Step S5, using cemented carbide as a hard core rod, and evenly coating the surface of the hard core rod with an oil lubricant, inserting the hard core rod into the tube blank to obtain an assembly, and deforming the assembly by hot drawing, the hot drawing temperature is 800° C., the speed is 5 m / min, and the single-pass deformation is controlled at 10%. When the total deformation reaches 40%, the tube is intermediate annealed at a temperature of 750° C. for 1 min, and the cycle is repeated for multiple times to obtain a tube blank with an outer diameter of 4.0 mm and an inner diameter of 3.68 mm.

[0107] Step S6, using red copper as a soft core rod, evenly coating the surface of the soft core rod with molybdenum disulfide, inserting the soft core rod into the tube blank to obtain an assembly, using room temperature drawing equipment to continuously cold draw the assembly, and controlling the deformation of a single pass to be 15%. When the total deformation reaches 45%, performing intermediate annealing on the assembly at a temperature of 620° C. for 1 min, repeating the process for multiple times to obtain an assembly with an outer diameter of 2.0 mm and an inner diameter of 1.71 mm, and then removing the soft core rod to obtain a tube.

[0108] Step S7, perform a multi-process coupled heat treatment of electric pulse treatment + aging treatment on the pipe, the electric pulse treatment process parameters are duty cycle P of 0.18, pulse frequency f of 300 Hz, and on-time of 600 μs, and the aging treatment process parameters are temperature of 310° C. and time of 36 h.

[0109] Step S8, the outer surface of the pipe is centerlessly ground, and then the pipe is electrochemically polished. The polishing liquid consists of 21% perchloric acid (HCLO4, content 70.0-70.2%) and 79% glacial acetic acid (CH3COOH, content not less than 99.5%) by volume fraction. The electrolytic polishing is performed at a constant voltage of 10V and room temperature for 6 minutes. The roughness of the outer surface of the pipe after polishing is 0.29μm, and the roughness of the inner surface is 0.74μm.

[0110] Step S9, cutting the nickel-titanium alloy tube into a length of 120 mm, and then performing femtosecond laser cutting on it, setting the pulse width to 100 fs, the pulse energy to 80 μJ, the pulse repetition frequency to 100 kHz, the cutting speed to 0.8 mm / s, and cutting under helium. After cutting, the heat treatment temperature is 540°C, the time is 25 min, and then the furnace cooling method is adopted to finally obtain the finished nickel-titanium alloy nasolacrimal duct stent.

[0111] Comparative Example 1

[0112] This comparative example provides a processing and preparation method, comprising the following steps:

[0113] Step S1, the nickel-titanium alloy rod is made according to the following mass percentage: Ni is 55.97%, C is 0.0046%, Co: <0.010%, Cu: <0.005%, Cr: <0.005%, H: <0.001%, Fe: <0.005%, Nb: <0.005%, N: <0.003%, O: 0.032%, and the remainder is Ti. The diameter of the nickel-titanium alloy rod is 24 mm, and the fixed length is 2 m. After cutting, it is straightened by electric straightening equipment. The straightness of the rod after straightening is 0.35 mm / m.

[0114] Step S2, cutting the straightened bar into a fixed length of 500 mm. The difference from the above embodiment is that this comparative embodiment uses electric spark combined with wire cutting equipment to drill holes in the bar, and the inner hole diameter of the tube blank is 19.0 mm.

[0115] Step S3, polishing the outer surface of the tube blank by a centerless grinder, and polishing the inner surface of the tube blank by an abrasive flow device. After grinding and polishing, the roughness of the outer surface of the tube blank is 0.24 μm, and the roughness of the inner surface is 0.68 μm.

[0116] Step S4, using cemented carbide as a hard core rod, and evenly coating the surface of the hard core rod with an oil lubricant, inserting the hard core rod into the tube blank to obtain an assembly, deforming the assembly by cold rolling, and controlling the deformation amount of a single pass to be 10%. When the total deformation amount reaches 30%, performing intermediate vacuum annealing on the tube, the annealing temperature is 800° C., the time is 6 min, and the cycle is repeated for multiple times to obtain a tube blank with an outer diameter of 10.0 mm and an inner diameter of 6.4 mm.

[0117] Step S5, using cemented carbide as a hard core rod, and evenly coating the surface of the hard core rod with an oil lubricant, inserting the hard core rod into the tube blank to obtain an assembly, and deforming the assembly by hot drawing, the hot drawing temperature is 800° C., the speed is 5 m / min, and the single-pass deformation is controlled at 10%. When the total deformation reaches 40%, the tube is intermediate annealed at a temperature of 750° C. for 1 min, and the cycle is repeated for multiple times to obtain a tube blank with an outer diameter of 4.0 mm and an inner diameter of 3.68 mm.

[0118] Step S6, using red copper as a soft core rod, evenly coating the surface of the soft core rod with molybdenum disulfide, inserting the soft core rod into the tube blank to obtain an assembly, using room temperature drawing equipment to continuously cold draw the assembly, and controlling the deformation of a single pass to be 15%. When the total deformation reaches 45%, performing intermediate annealing on the assembly at a temperature of 620° C. for 1 min, repeating the process for multiple times to obtain an assembly with an outer diameter of 2.0 mm and an inner diameter of 1.71 mm, and then removing the soft core rod to obtain a tube.

[0119] Step S7, perform a multi-process coupled heat treatment of electric pulse treatment + aging treatment on the pipe, the electric pulse treatment process parameters are duty cycle P of 0.18, pulse frequency f of 300 Hz, and on-time of 600 μs, and the aging treatment process parameters are temperature of 310° C. and time of 36 h.

[0120] Step S8, the outer surface of the pipe is centerlessly ground, and then the pipe is electrochemically polished. The polishing liquid consists of 21% perchloric acid (HCLO4, content 70.0-70.2%) and 79% glacial acetic acid (CH3COOH, content not less than 99.5%) by volume fraction. The electrolytic polishing is performed at a constant voltage of 10V and room temperature for 6 minutes. The roughness of the outer surface of the pipe after polishing is 0.58μm, and the roughness of the inner surface is 2.41μm.

[0121] Step S9, cutting the nickel-titanium alloy tube into a length of 120 mm, and then performing femtosecond laser cutting on it, setting the pulse width to 100 fs, the pulse energy to 80 μJ, the pulse repetition frequency to 100 kHz, the cutting speed to 0.8 mm / s, and cutting under helium. After cutting, the heat treatment temperature is 540°C, the time is 25 min, and then the furnace cooling method is adopted to finally obtain the finished nickel-titanium alloy nasolacrimal duct stent.

[0122] Comparative Example 2

[0123] This comparative example provides a processing and preparation method, comprising the following steps:

[0124] Step S1, the nickel-titanium alloy rod is made according to the following mass percentage: Ni is 55.97%, C is 0.0046%, Co: <0.010%, Cu: <0.005%, Cr: <0.005%, H: <0.001%, Fe: <0.005%, Nb: <0.005%, N: <0.003%, O: 0.032%, and the remainder is Ti. The diameter of the nickel-titanium alloy rod is 24 mm, and the fixed length is 2 m. After cutting, it is straightened by electric straightening equipment. The straightness of the rod after straightening is 0.35 mm / m.

[0125] Step S2, the straightened bar is cut into a fixed length of 500 mm, and the bar is drilled using a deep hole processing device, and the inner hole diameter of the tube blank is 19.0 mm.

[0126] Step S3, polishing the outer surface of the tube blank by a centerless grinder, and polishing the inner surface of the tube blank by an abrasive flow device. After grinding and polishing, the roughness of the outer surface of the tube blank is 0.24 μm, and the roughness of the inner surface is 0.68 μm.

[0127] Step S4, using cemented carbide as a hard core rod, and evenly coating the surface of the hard core rod with an oil lubricant, inserting the hard core rod into the tube blank to obtain an assembly, and deforming the assembly by hot drawing, the hot drawing temperature is 800° C., the speed is 3 m / min, and the single-pass deformation is controlled at 10%. When the total deformation reaches 30%, the tube is intermediate annealed at a temperature of 750° C. for 2 min, and the cycle is repeated for multiple times to obtain a tube blank with an outer diameter of 4.0 mm and an inner diameter of 3.68 mm.

[0128] Step S5, using red copper as a soft core rod, uniformly coating the surface of the soft core rod with molybdenum disulfide, inserting the soft core rod into the tube blank to obtain an assembly, using room temperature drawing equipment to continuously cold draw the assembly, and controlling the deformation of a single pass to be 15%. When the total deformation reaches 45%, performing intermediate annealing on the assembly, the annealing temperature is 620° C., the time is 1 min, and the cycle is repeated for multiple times to obtain an assembly with an outer diameter of 2.0 mm and an inner diameter of 1.71 mm, and then removing the soft core rod to obtain a tube.

[0129] Step S6, performing a multi-process coupled heat treatment of electric pulse treatment + aging treatment on the pipe, the electric pulse treatment process parameters are duty cycle P of 0.18, pulse frequency f of 300 Hz, and on-time of 600 μs, and the aging treatment process parameters are temperature of 310° C. and time of 36 h.

[0130] Step S7, the outer surface of the pipe is centerlessly ground, and then the pipe is electrochemically polished. The polishing liquid consists of 21% perchloric acid (HCLO4, content 70.0-70.2%) and 79% glacial acetic acid (CH3COOH, content not less than 99.5%) by volume fraction. The electrolytic polishing is performed at a constant voltage of 10V and room temperature for 6 minutes. The roughness of the outer surface of the pipe after polishing is 0.31μm, and the roughness of the inner surface is 0.75μm.

[0131] Step S8, cutting the nickel-titanium alloy tube into a length of 120 mm, and then performing femtosecond laser cutting on it, setting the pulse width to 100 fs, the pulse energy to 80 μJ, the pulse repetition frequency to 100 kHz, the cutting speed to 0.8 mm / s, and cutting under helium. After cutting, the heat treatment temperature is 540°C, the time is 25 min, and then the furnace cooling method is adopted to finally obtain the finished nickel-titanium alloy nasolacrimal duct stent.

[0132] Comparative Example 3

[0133] This comparative example provides a processing and preparation method, comprising the following steps:

[0134] Step S1, the nickel-titanium alloy rod is made according to the following mass percentage: Ni is 55.97%, C is 0.0046%, Co: <0.010%, Cu: <0.005%, Cr: <0.005%, H: <0.001%, Fe: <0.005%, Nb: <0.005%, N: <0.003%, O: 0.032%, and the remainder is Ti. The diameter of the nickel-titanium alloy rod is 24 mm, and the fixed length is 2 m. After cutting, it is straightened by electric straightening equipment. The straightness of the rod after straightening is 0.35 mm / m.

[0135] Step S2, the straightened bar is cut into a fixed length of 500 mm, and the bar is drilled using a deep hole processing device, and the inner hole diameter of the tube blank is 19.0 mm.

[0136] Step S3, polishing the outer surface of the tube blank by a centerless grinder, and polishing the inner surface of the tube blank by an abrasive flow device. After grinding and polishing, the roughness of the outer surface of the tube blank is 0.24 μm, and the roughness of the inner surface is 0.68 μm.

[0137] Step S4, using cemented carbide as a hard core rod, and evenly coating the surface of the hard core rod with an oil lubricant, inserting the hard core rod into the tube blank to obtain an assembly, deforming the assembly by cold rolling, and controlling the deformation amount of a single pass to be 10%. When the total deformation amount reaches 30%, performing intermediate vacuum annealing on the tube, the annealing temperature is 800° C., the time is 6 min, and the cycle is repeated for multiple times to obtain a tube blank with an outer diameter of 10.0 mm and an inner diameter of 6.4 mm.

[0138] Step S5, which is different from the above embodiment, is that this comparative embodiment uses aluminum alloy as a hard core rod, and molybdenum disulfide is evenly coated on the surface of the hard core rod, and the hard core rod is inserted into the tube blank to obtain an assembly, and the assembly is subjected to hot drawing and diameter reduction, and the deformation amount of a single pass is controlled at 12%. When the total deformation amount reaches 45%, the tube is subjected to intermediate annealing at a temperature of 720° C. for 1 min, and the cycle is repeated for multiple times to obtain a tube blank with an outer diameter of 2.0 mm and an inner diameter of 1.71 mm.

[0139] Step S6, performing a multi-process coupled heat treatment of electric pulse treatment + aging treatment on the pipe, the electric pulse treatment process parameters are duty cycle P of 0.18, pulse frequency f of 300 Hz, and on-time of 600 μs, and the aging treatment process parameters are temperature of 310° C. and time of 36 h.

[0140] Step S7, the outer surface of the pipe is centerlessly ground, and then the pipe is electrochemically polished. The polishing liquid consists of 21% perchloric acid (HCLO4, content 70.0-70.2%) and 79% glacial acetic acid (CH3COOH, content not less than 99.5%) by volume. The electrolytic polishing is performed at a constant voltage of 10V and room temperature for 6 minutes. The roughness of the outer surface of the pipe after polishing is 0.48μm, and the roughness of the inner surface is 1.81μm.

[0141] Step S8, cutting the nickel-titanium alloy tube into a length of 120 mm, and then performing femtosecond laser cutting on it, setting the pulse width to 100 fs, the pulse energy to 80 μJ, the pulse repetition frequency to 100 kHz, the cutting speed to 0.8 mm / s, and cutting under helium. After cutting, the heat treatment temperature is 540°C, the time is 25 min, and then the furnace cooling method is adopted to finally obtain the finished nickel-titanium alloy nasolacrimal duct stent.

[0142] Comparative Example 4

[0143] This comparative example provides a processing and preparation method, comprising the following steps:

[0144] Step S1, the nickel-titanium alloy rod is made according to the following mass percentage: Ni is 55.97%, C is 0.0046%, Co: <0.010%, Cu: <0.005%, Cr: <0.005%, H: <0.001%, Fe: <0.005%, Nb: <0.005%, N: <0.003%, O: 0.032%, and the remainder is Ti. The diameter of the nickel-titanium alloy rod is 24 mm, and the fixed length is 2 m. After cutting, it is straightened by electric straightening equipment. The straightness of the rod after straightening is 0.35 mm / m.

[0145] Step S2, cutting the straightened bar into a fixed length of 500 mm. The difference from the above embodiment is that this comparative embodiment uses electric spark combined with wire cutting equipment to drill holes in the bar, and the inner hole diameter of the tube blank is 19.0 mm.

[0146] Step S3, polishing the outer surface of the tube blank by a centerless grinder, and polishing the inner surface of the tube blank by an abrasive flow device. After grinding and polishing, the roughness of the outer surface of the tube blank is 0.24 μm, and the roughness of the inner surface is 0.68 μm.

[0147] Step S4, using cemented carbide as a hard core rod, and evenly coating the surface of the hard core rod with an oil lubricant, inserting the hard core rod into the tube blank to obtain an assembly, deforming the assembly by cold rolling, and controlling the deformation amount of a single pass to be 10%. When the total deformation amount reaches 30%, performing intermediate vacuum annealing on the tube, the annealing temperature is 800° C., the time is 6 min, and the cycle is repeated for multiple times to obtain a tube blank with an outer diameter of 10.0 mm and an inner diameter of 6.4 mm.

[0148] Step S5, using cemented carbide as a hard core rod, and evenly coating the surface of the hard core rod with an oil lubricant, inserting the hard core rod into the tube blank to obtain an assembly, and deforming the assembly by hot drawing, the hot drawing temperature is 800° C., the speed is 5 m / min, and the single-pass deformation is controlled at 10%. When the total deformation reaches 40%, the tube is intermediate annealed at a temperature of 750° C. for 1 min, and the cycle is repeated for multiple times to obtain a tube blank with an outer diameter of 4.0 mm and an inner diameter of 3.68 mm.

[0149] Step S6, using red copper as a soft core rod, evenly coating the surface of the soft core rod with molybdenum disulfide, inserting the soft core rod into the tube blank to obtain an assembly, using room temperature drawing equipment to continuously cold draw the assembly, and controlling the deformation of a single pass to be 15%. When the total deformation reaches 45%, performing intermediate annealing on the assembly at a temperature of 620° C. for 1 min, repeating the process for multiple times to obtain an assembly with an outer diameter of 2.0 mm and an inner diameter of 1.71 mm, and then removing the soft core rod to obtain a tube.

[0150] Step S7 is different from the above embodiment in that, in this comparative embodiment, the pipe is heat treated with process parameters of temperature 500° C. and time 50 min.

[0151] Step S8, the outer surface of the pipe is centerlessly ground, and then the pipe is electrochemically polished. The polishing liquid consists of 21% perchloric acid (HCLO4, content 70.0-70.2%) and 79% glacial acetic acid (CH3COOH, content not less than 99.5%) by volume fraction, respectively. The electrolytic polishing is performed at a constant voltage of 10V and room temperature for 6 minutes. The roughness of the outer surface of the pipe after polishing is 0.30μm, and the roughness of the inner surface is 0.82μm.

[0152] Step S9, cutting the nickel-titanium alloy tube into a length of 120 mm, and then performing femtosecond laser cutting on it, setting the pulse width to 100 fs, the pulse energy to 80 μJ, the pulse repetition frequency to 100 kHz, the cutting speed to 0.8 mm / s, and cutting under helium. After cutting, the heat treatment temperature is 540°C, the time is 25 min, and then the furnace cooling method is adopted to finally obtain the finished nickel-titanium alloy nasolacrimal duct stent.

[0153] The following Table 1 shows the performance test results of the nickel-titanium alloy tubes obtained in three embodiments of the present invention and four comparative embodiments.

[0154]

[0155] It can be seen from the above comparative performance test results that the nickel-titanium alloy nasolacrimal duct stent produced by the processing and preparation method of the new nickel-titanium alloy nasolacrimal duct stent provided by the present invention has more excellent tensile strength, upper platform strength and lower platform strength, higher uniform strain and lower residual strain, lower outer surface roughness and inner surface roughness, which proves that the nickel-titanium alloy nasolacrimal duct stent produced by the present invention has good flexibility and supporting strength, and meets the requirements of the nasolacrimal duct stent for raw material performance.

[0156] The above are only specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A novel method for processing and preparing a nickel-titanium alloy nasolacrimal duct stent, characterized in that: The following steps are involved: S1, obtaining a nickel-titanium alloy bar, and straightening the nickel-titanium alloy bar to form a straight bar; S2, mechanically drilling the straight rod to form a rough tube blank; S3, polishing the inner surface and outer surface of the rough tube blank; S4, using a hard mandrel to cold-roll the rough tube to form a tube with a diameter of 4.0-8.0 mm; S5, using a hard mandrel to perform hot drawing deformation on the tube blank to form a tube blank with a diameter of Φ1.0-4.0 mm; S6, using a soft mandrel to perform room temperature drawing deformation on the tube blank to form a tube with a diameter of Φ0.25-2.0 mm; S7, performing multi-process coupled heat treatment on the pipe; S8, performing centerless grinding on the pipe and electrochemical polishing on the pipe; S9. Laser cutting the tube and vacuum heat treatment the tube to obtain a novel nickel-titanium alloy nasolacrimal duct stent.

2. The method for processing and preparing the novel nickel-titanium alloy nasolacrimal duct stent according to claim 1, characterized in that: The nickel-titanium alloy bar material in step S1 is prepared according to the following mass percentages: Ni is 54.5-57.0%, C≤0.04%, Co≤0.05%, Cu≤0.01%, Cr≤0.01%, H≤0.005%, Fe≤0.05%, Nb≤0.025%, N≤0.005%, O≤0.04%, and the balance is Ti; The fixed length of the nickel-titanium alloy bar is 1-4m. After being cut into the fixed length, it is straightened by a straightening device, and the straightness after straightening is not greater than 0.5mm / m.

3. The method for processing and preparing the novel nickel-titanium alloy nasolacrimal duct stent according to claim 1, characterized in that: In step S2, before mechanical drilling is performed on the straight rod, the straight rod is processed into a fixed length after being straightened.

4. The method for processing and preparing the novel nickel-titanium alloy nasolacrimal duct stent according to claim 1, characterized in that: In step S3, the inner surface and the outer surface of the rough tube blank are polished by mechanical polishing equipment, and the roughness of the inner surface after polishing is not greater than 1.6 μm, and the roughness of the outer surface is not greater than 1.0 μm.

5. The method for processing and preparing the novel nickel-titanium alloy nasolacrimal duct stent according to claim 1, characterized in that: In step S4, the material of the hard core rod is cemented carbide, and the hard core rod is inserted into the rough tube blank to obtain an assembly, and the assembly is cold-rolled and deformed by cold rolling equipment, and the deformation amount of a single pass is less than 13%. After the deformation amount is 25%-50%, intermediate vacuum annealing is performed, and after multiple cycles, a tube blank of Φ4.0-8.0mm is formed.

6. The method for processing and preparing the novel nickel-titanium alloy nasolacrimal duct stent according to claim 1, characterized in that: In step S5, the material of the hard core rod is cemented carbide, and the hard core rod is inserted into the tube blank to obtain a combination, and the combination is hot-drawn by a hot drawing device, and the deformation amount of a single pass is less than 15%. After the deformation amount is 30%-60%, intermediate annealing is performed, and after multiple cycles, a tube blank of Φ1.0-4.0mm is formed.

7. The method for processing and preparing the novel nickel-titanium alloy nasolacrimal duct stent according to claim 1, characterized in that: In step S6, the material of the soft core rod is a material with a Vickers hardness of less than 100. The soft core rod with a surface coated with molybdenum disulfide lubricant is inserted into the tube blank to obtain an assembly. The assembly is cold-drawn by room temperature drawing equipment. The deformation amount of a single pass is less than 20%. After the deformation amount is 30%-60%, intermediate annealing is performed. After multiple cycles, an assembly of Φ0.25-2.0 mm is formed. Then, the assembly is cored to obtain a Φ0.25-2.0 mm tube.

8. The method for processing and preparing the novel nickel-titanium alloy nasolacrimal duct stent according to claim 1, characterized in that: In step S7, the pipe is heat treated by a multi-process coupling method of electric pulse treatment and aging treatment.

9. The method for processing and preparing the novel nickel-titanium alloy nasolacrimal duct stent according to claim 1, characterized in that: In step S8, when the tube is electrochemically polished, the polishing liquid consists of perchloric acid and glacial acetic acid with volume fractions of 15-25% and 75-85%, respectively, the constant voltage is 5-20V, the electrolytic polishing is carried out at room temperature, the polishing time is 1-30 minutes, and the roughness of the inner surface after polishing is less than 1.0μm, and the roughness of the outer surface is less than 0.5μm.

10. The method for processing and preparing the novel nickel-titanium alloy nasolacrimal duct stent according to claim 1, characterized in that: In step S9, the tube is first cut into the corresponding length of the nasolacrimal duct stent, and then femtosecond laser cutting is performed. The tube is then vacuum heat treated at a temperature of 400-600°C for 10-50 minutes, and then cooled by furnace cooling or water cooling.

Citation Information

Patent Citations

  • Method and equipment for improving shape memory alloy superelasticity

    CN103352194A

  • Method for endowing Ni-enriched TiNi shape memory alloy with two-way shape memory characteristic

    CN108977696A

  • Manufacturing method of W fiber reinforced TiNi alloy pipe with high X-ray visibility

    CN113025929A

  • Processing method of novel medical titanium alloy coronary artery drug coating stent

    CN115069957A

  • METHOD FOR PRODUCING COLD-DEFORMED SEAMLESS PIPES MADE OF TITANIUM ALLOY Ti-3Al-2,5V

    RU2583566C1